Genetic susceptibility to environmental carcinogenesis in Slovenian melanoma patients - Dolžan, Vita (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
The skin acts as the first defence barrier against external environmental pollutants, including chemicals and UV radiation. Cytochrome P450 CYP1A1 and glutathione S-transferases (GSTs) found in melanocytes and skin basal layers were shown to participate both in the metabolism of xenobiotics and in detoxification of reactive oxygen species (ROS). In our study we analysed the distribution of single and combined CYP1A1, GSTMI, GSTTI and GSTP1 genotypes contributing to inter-individual differences in metabolism of xenobiotics and ROS in 125 Slovenian healthy individuals and in 140 patients with sporadic malignant melanoma. Our results showed no statistically significant differences between melanoma patients and healthy controls in the frequency ofpolymorphic CYP1A1 and GST genotypes. The risk of developing melanoma was not significantly increased in individuals homo- or heterozygous for the CYP1A1'"2A allele combined with GSTM1'0 genotype (OR: 1.86; 95 % CI: 0.36-7.71), but increased slightly in carriers of CYP1A1 "2A combined with both GSTM1 *0 and GSTTI *0 genotypes (OR: 3.42; 95 % CI: 0.36-29.6). Our results indicate that factors other than the polymorphic genes coding xenobiotic metabolising enzymes play a major role in protection against environmental carcinogenesis in human skin.
Keywords: Citokrom P-450 CYP1A1; Cytochrome P-450 Cyp1a1; dejavniki okolja; dermatologija; Genetics; genetika; Genotip; Genotype; Glutathione Transferases; karcinogeneza; Kisik, aktivne oblike; Melanom; Melanoma; polimorfizem; Polimorfizem (genetika); Polymorphism (Genetics); Reactive Oxygen Species